2020
DOI: 10.21203/rs.2.19106/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health inequity in workers of Latin America and the Caribbean

Abstract: Abstract Background: Latin America and the Caribbean (LAC) is the world’s most inequitable region in terms of wealth distribution. The full scale of social inequalities in health has been hidden by the lack of reliable data. This study aimed to measure and compare health inequalities in the working population within and between 15 countries of LAC. Methods: A sample of 180 163 workers aged 18 years and older was drawn from t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The 33 countries of Latin America and the Caribbean (LAC) comprise the most inequitable regions of the world, resulting in a significant impact on the health of its population. 4 Historically, most LAC countries have had two separate public sector systems: a social security system, which is better financed and offers comprehensive benefits; and a noncontributory system, which serves vulnerable populations. They also have a private insurance system that includes alternative supplementary coverage disproportionately provided for wealthy groups.…”
mentioning
confidence: 99%
“…The 33 countries of Latin America and the Caribbean (LAC) comprise the most inequitable regions of the world, resulting in a significant impact on the health of its population. 4 Historically, most LAC countries have had two separate public sector systems: a social security system, which is better financed and offers comprehensive benefits; and a noncontributory system, which serves vulnerable populations. They also have a private insurance system that includes alternative supplementary coverage disproportionately provided for wealthy groups.…”
mentioning
confidence: 99%
“…A study in Brazil revealed that informal part-time workers reported arthritis, bronchitis, heart disease, cirrhosis, depression and chronic disease more often than their counterparts in full-time with social protection [17]. Also, a study in 15 Latin American countries found that manual (skilled and nonskilled) jobs had the highest P-SPH, and that around 42% of P-SPH in men and 31% in women could be avoided if they had the working and employment conditions of the workers in non-manual skilled jobs [18]. Due to lack of government control, working conditions in informal employment are frequently not in accordance with health and safety laws often to avoid costs associated to regulation's requirements (safety training or protective equipment) or to pay lower salaries.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were similar between women and men. However, several studies have observed that lack of social support from colleagues and particularly from employers, as well as high quantitative demands at work, may affect SHS among women to a greater extent [23,24,25,26,27]. In this sense, it would be useful for organizations in general and human resources personnel more specifically to design strategies aiming to strengthen collaboration in the workplace.…”
Section: Discussionmentioning
confidence: 99%